Chloride-ion-directed synthesis of plate-like Cu2O mesocrystals for effective nitrogen fixation. Issue 40 (7th October 2022) - Wang, Jie; Tang, Fu; Gao, Junheng; Yao, Chuang; Zhang, Sheng; Li, Lidong
Abstract : Plate-like Cu2 O mesocrystals are synthesized under the regulation of Cl − and polyacrylamide (PAM), and they show an efficient N2 -fixation ability. Abstract : Cuprous oxide (Cu2 O) mesocrystals, which are composed of numerous nanocrystals with a common crystallographic orientation, are supposed to possess superior photocatalytic abilities than the normal constructions, but very few of them have been reported to date. In this work, plate-like Cu2 O mesocrystals were successfully fabricated via a facile one-pot wet chemical strategy. Unlike the commonly used polymers or small molecules, chloride ions (Cl − ) were employed as structure-directing agents and played the main role in the Cu2 O mesocrystal formation. The formation mechanism was interpreted as follows: the presence of Cl − inhibited the formation of CuO and Cu by forming the intermediate product CuCl, which was further hydrolyzed to Cu2 O nanocrystals. Cl − tended to adsorb on the (111) facets of the formed Cu2 O nanocrystals and stabilize them. Then the Cu2 O nanocrystals were aligned side by side through the unabsorbed side faces, leading to mutual nanocrystals orientation and crystallographic lock-in, facilitating the formation of plate-like Cu2 O mesocrystals. The polymer, polyacrylamide (PAM), also promoted the mesocrystals formation by serving as a stabilizer and fixed the crystallographic orientation of the Cu2 O nanocrystals during their orderly stacking process. The plate-like Cu2 O mesocrystals showed a long decay time and pronounced performance toward the visible-light-driven photocatalytic reduction of N2 into NH3 . This research may stimulate in-depth investigations into the exploration of new synthetic methods for the design and construction of novel mesocrystals.